Integrin-linked kinase expression in myeloid cells promotes colon tumorigenesis - Ahmed, Afsar U.; Almasabi, Saleh; Firestein, Ron; Williams, Bryan R.G. (Frontiers in Immunology, 2023)
Colorectal cancer (CRC) is one of the most common forms of cancer worldwide and treatment options for advanced CRC, which has a low 5-year survival rate, remain limited. Integrinlinked kinase (ILK), a multifunctional, scaffolding, pseudo-kinase regulating many integrinmediated cellular processes, is highly expressed in many cancers. However, the role of ILK in cancer progression is yet to be fully understood. We have previously uncovered a proinflammatory role for myeloid-specific ILK in dextran sodium sulfate (DSS)-induced colitis. To establish a correlation between chronic intestinal inflammation and colorectal cancer (CRC), we investigated the role of myeloid-ILK in mouse models of CRC. When myeloid-ILK deficient mice along with the WT control mice were subjected to colitis-associated and APC min/+ -driven CRC, tumour burden was reduced by myeloid-ILK deficiency in both models. The tumour-promoting phenotype of macrophages, M2 polarization, in vitro was impaired by the ILK deficiency and the number of M2-specific marker CD206-expressing tumourassociated macrophages (TAMs) in vivo were significantly diminished in myeloid-ILK deficient mice. Myeloid-ILK deficient mice showed enhanced tumour infiltration of CD8+ T cells and reduced tumour infiltration of FOXP3+ T cells in colitis-associated and APC min/+driven CRC, respectively, with an overall elevated CD8+/FOXP3+ ratio suggesting an antitumour immune phenotypes. In patient CRC tissue microarrays we observed elevated ILK+ myeloid (ILK+ CD11b+) cells in tumour sections compared to adjacent normal tissues, suggesting a conserved role for myeloid-ILK in CRC development in both human and animal models. This study identifies myeloid-specific ILK expression as novel driver of CRC, which could be targeted as a potential therapeutic option for advanced disease.